Prevalence and antimicrobial susceptibility of Salmonella and Shigella species isolated from diarrheic children in Ambo town - Wagi Tosisa; Adane Mihret; Asnake Ararsa; Tadesse Eguale; Tamrat Abebe (BMC, 2020)
Abstract Background Diarrhea, particularly of enteric bacterial pathogen, remains a major cause of morbidity and mortality in Ethiopia. Despite the high prevalence of diarrheal disease among under-five children, antibiotic resistance of bacterial pathogens test is not part of routine childcare in the study area. This study aimed to investigate the prevalence and antimicrobial susceptibility status of Salmonella and Shigella species among diarrheic children attending public health institutions in Ambo town, west Showa, Ethiopia. Methods Institutional based, cross-sectional study was carried out from January to July 2014 among 239 diarrheic children below five years of age in Ambo town, Ethiopia. Information about patient demographics, signs, and symptoms was obtained from the parents/guardians of each child using a questionnaire. Stool samples from diarrheic children were collected and processed for isolation of Salmonella and Shigella using conventional microbiology procedures. Suspected Salmonella isolates were confirmed by genus-specific PCR and serotyped using a slide agglutination test. Susceptibility to 10 commonly used antimicrobials was assessed using the Kirby Bauer disc diffusion method. Results From the 239 children screened, only nine (3.8%) of them were positive for either Salmonella (n = 3) or Shigella (n = 6) and 19 (7.9%) positive for the intestinal parasite. Three species of Shigella were identified: Shigella flexinari (n = 3), Shigella boydii (n = 2), and Shigella sonnei (n = 1). The three Salmonella isolates were S. chicago, S. caracas, and S. saintpaul. Salmonella and Shigella isolates were resistant to ampicillin (88.9%), followed by tetracycline (66.7%), cotrimoxazole (55.6%), chloramphenicol (44.4%), amoxicillin (33.3%), nalidixic acid (11.1%) and cefotaxime (11.1%). All isolates were sensitive to amikacin, ciprofloxacin, and gentamycin. Conclusion In this study, either Salmonella or Shigella species were detected only in 3.8% of diarrheic children in Ambo town, suggesting the dominance of other causes of diarrhea in the study area. A further study targeting other causes of diarrhea should be conducted to establish the major causes of childhood diarrhea in the study area.